2004
DOI: 10.1523/jneurosci.3141-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Locking the Dimeric GABABG-Protein-Coupled Receptor in Its Active State

Abstract: G-protein-coupled receptors (GPCRs) play a major role in cell-cell communication in the CNS. These proteins oscillate between various inactive and active conformations, the latter being stabilized by agonists. Although mutations can lead to constitutive activity, most of these destabilize inactive conformations, and none lock the receptor in an active state. Moreover, GPCRs are known to form dimers, but the role of each protomer in the activation process remains unclear. Here, we show that the heterodimeric GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 52 publications
5
48
0
1
Order By: Relevance
“…Previous studies have shown that receptor activation results from the closure of the VFT upon agonist binding (9,(11)(12)(13)(14)(15). This conformational change in the extracellular domain is coupled to a conformational change in the intracellular side of at least one 7TM that is responsible for G-protein coupling (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Previous studies have shown that receptor activation results from the closure of the VFT upon agonist binding (9,(11)(12)(13)(14)(15). This conformational change in the extracellular domain is coupled to a conformational change in the intracellular side of at least one 7TM that is responsible for G-protein coupling (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Structural and mutagenesis studies indicated that the closure of the VFT resulting from agonist binding in the cleft represents a key step in receptor activation (12)(13)(14)(15)(16). It is assumed that this VFT conformational change is associated with a reorientation of the two VFTs in these dimeric receptors (15,16), leading to a relative movement of the two 7TMs and the activation of one of them (17).…”
mentioning
confidence: 99%
“…Recently, activation of some class A (rhodopsin-like) GPCRs has been monitored in real-time by using a fluorescence resonance energy transfer (FRET)-based approach (6). The FRET responses observed upon agonist binding were well described by monoexponential fits whose time constants were faster than previously expected: approximately 40 ms for the ␣ 2A -adrenergic receptor (7), 70 ms for the A 2A -adenosine receptor (8), and 60 ms for the ␤ 1 -adrenergic receptor (9), although not as fast as for light receptor rhodopsin (10) and ligand-gated ion channels (11).A distinctive feature of class C GPCRs is a very large extracellular domain (12), comprising a noteworthy Venus Flytrap module (VFTM), a bilobate structure in the cleft of which the agonist binds and induces its closure (13,14). Compared with other classes, the overall conformational change leading to activation of class C GPCRs appears more complex since it is preceded by the closure of the VFTM (12), an additional step that may delay activation.…”
mentioning
confidence: 99%